2015
DOI: 10.1039/c4dt03054k
|View full text |Cite
|
Sign up to set email alerts
|

Cationic, luminescent cyclometalated iridium(iii) complexes based on substituted 2-phenylthiazole ligands

Abstract: Ten cationic heteroleptic iridium(III) complexes, [Ir(emptz)2(N^N)](PF6) were prepared from a cyclometalated iridium bridged-chloride dimer involving two ethyl-4-methylphenylthiazole-5-carboxylate (emptz) ligands. One X-ray crystallographic study was undertaken where the ancillary N^N ligand was 4,7-diphenyl-1,10-phenanthroline and revealed the anticipated structure, showing a distorted octahedral coordination geometry at Ir(III). The complexes were visibly luminescent with modestly structured emission at 540-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
(48 reference statements)
0
2
1
Order By: Relevance
“…In consequence, the use of F and/or F‐containing groups as electron withdrawing substituents has been dropped as a design concept for green emitting LECs and the design and synthesis of fluorine‐free Ir‐iTMCs for LEC application has been pursued. Other electron withdrawing (EW) groups such as sulfur containing groups (e.g., sulfanyl and sulfone) as well as other EW C ^ N ligands like methoxy/methyl substituted 2,3′‐bipyridines have been explored in the attempt to get fluorine‐free green emitting Ir‐iTMCs. Unfortunately, these fluorine‐free Ir‐iTMCs did not lead to an improvement in LEC device lifetime, thereby raising the question whether fluorine indeed is the primary cause of the short lifetime of green LEC devices based on fluorinated iTMCs.…”
Section: Introductioncontrasting
confidence: 96%
“…In consequence, the use of F and/or F‐containing groups as electron withdrawing substituents has been dropped as a design concept for green emitting LECs and the design and synthesis of fluorine‐free Ir‐iTMCs for LEC application has been pursued. Other electron withdrawing (EW) groups such as sulfur containing groups (e.g., sulfanyl and sulfone) as well as other EW C ^ N ligands like methoxy/methyl substituted 2,3′‐bipyridines have been explored in the attempt to get fluorine‐free green emitting Ir‐iTMCs. Unfortunately, these fluorine‐free Ir‐iTMCs did not lead to an improvement in LEC device lifetime, thereby raising the question whether fluorine indeed is the primary cause of the short lifetime of green LEC devices based on fluorinated iTMCs.…”
Section: Introductioncontrasting
confidence: 96%
“…In addition to the above identified intrinsic σ-antibonding structural instability of Ir-iTMCs, it has been observed that fluorine substitution adds to the shortening of device lifetime for Ir-iTMC-LECs. , Support for this hypothesis is, that in OLEDs (organic light emitting diodes) cleavage of the C-F bond in a blue neutral complex (FIrpic) has been held responsible for a significant shortening of its OLED device lifetime . For that reason fluorine-containing Ir-iTMCs have then been abandoned for green emitting LECs and the focus of research has shifted toward finding fluorine free Ir-iTMCs that emit green light. However, it turned out that these fluorine free complexes did not meet the expectations and did not yield LECs with improved lifetime, indicating that per se fluorine substitution of the C^N ligand may not be the main reason for the short device lifetime of green LECs based on fluorinated Ir-iTMCs (F-Ir-iTMCs). Recently, we studied a series of green emitting Ir-iTMCs [Ir­(4ppy) 2 (N^N)]­[PF 6 ] with 4Fppy = 2-(4-fluorophenyl)­pyridine) and N^N ligand being either 2,2′-bipyridine, 4.4′-dimethyl-2,2′-bipyridine, 5.5′-dimethyl-2,2′-bipyridine or 4.4′-di- tert -butyl-2,2′-bipyridine where we achieved, aside from excellent emission properties, a LEC based on the 2,2′-bipyridine containg complex that showed a lifetime of 668 h, which is appreciably high .…”
Section: Introductionmentioning
confidence: 99%
“…The proligands HL 1 and HL 2 were synthesized via typical condensation of 1,10-phenanthroline-5,6-dione with 4-pyridinecarboxaldehyde and 4-(4-pyridinyl)-benzaldehyde, respectively. , Compounds HL 1 and HL 2 were obtained in moderate to high yields of 52% and 70%, respectively.…”
Section: Resultsmentioning
confidence: 99%